Bendera One Piece di Bawah Bendera Pusaka: Analisis Semiotika Budaya Pop, Identitas Nasional, dan Imajinasi Demokratis dalam Poster Media Indonesia - Fathir Khalid; Dzikri Cahya Mahesa; Anwar Alwi Al Farizi; Iqhfa Qalbi; Dayudin Dayudin (Jurnal Lazuardi, 2026)
Abstract This study examines the phenomenon of the appearance of the One Piece flag alongside the Indonesian Red and White flag in an editorial poster published by Media Indonesia as a representation of a shift in how Indonesia’s younger generation understands national identity and democratic imagination. Employing Ferdinand de Saussure’s structural semiotics to dissect the system of signs, and Roland Barthes’ semiotic framework to uncover layers of myth and ideology, the study analyzes how global popular culture negotiates with local national symbols within the visual space of mass media. The method used is qualitative semiotic analysis with a descriptive–interpretive approach, treating the poster as a visual text. The findings indicate that the combination of the two flags produces a new sign system that reflects the hybridity of youth identity, in which democratic values are no longer imagined solely through conventional narratives of nationalism, but through the appropriation of popular culture symbols perceived to resonate with contemporary political aspirations. At the denotative level, the two flags function as signifiers carrying different signifieds national sovereignty versus individual freedom. However, at the connotative and mythological levels, this juxtaposition deconstructs the myth of a pure national identity and opens up space for a more inclusive and transnational democratic imagination. This study contributes to an understanding of how the political subjectivity of the digital generation is formed through negotiations between the local and the global, and how mass media plays a role in producing discourse on national identity in the transnational era. Keywords: semiotics, One Piece, national identity, popular culture, democratic imagination.